Polypyrimidine-tract binding protein (PTB) is necessary, but not sufficient, for efficient internal initiation of translation of human rhinovirus-2 RNA. - Hunt, S L (1999)
Initiation of translation of the animal picornavirus RNAs is via a mechanism of direct internal ribosome entry, which requires a substantial segment of the viral 5'-untranslated region, generally known as the IRES (for "internal ribosome entry site"). Because, however, translation of the RNAs of members of the enterovirus, and more especially, the rhinovirus subgroups of the Picornaviridae is restricted in the reticulocyte lysate system, but is greatly stimulated by the addition of HeLa cell extracts, the implication is that, in these cases, internal initiation also requires cellular trans-acting factors that are more abundant in HeLa cell extracts than in rabbit reticulocytes. This was used as the basis of a functional assay for the purification of the HeLa cell factors required for translation dependent on the human rhinovirus-2 (HRV) IRES. There are two such HeLa cell factors separable by ion-exchange chromatography, each of which is individually active in the assay, although their combined effect is synergistic. One of these activities is shown to be polypyrimidine-tract binding protein (PTB) on the grounds that (1) the activity copurifies to homogeneity with PTB and (2) recombinant PTB expressed in Escherichia coli stimulates HRV IRES-dependent translation with a specific activity similar to that of the purified HeLa cell factor. Furthermore, it is shown that recombinant PTB also stimulates the translation of RNAs bearing the poliovirus type 1 (Mahoney) IRES.